2023
DOI: 10.3390/heritage6050205
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Heritage of the Battle to Contain COVID-19 in Australia and Its Implications for Heritage Studies

Abstract: One of the major public health measures to manage and contain the outbreak of the COVID-19 pandemic was to engage in systematic contact tracing, which required gastronomy, community and sporting venues to keep patron registers. Stand-alone and web-based applications, developed by a range of private IT providers, soon replaced pen-and-paper lists. With the introduction of a uniform, state-wide, mandatory data collection system, these private applications became obsolete. Although only active for four months, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Private websites, however, are usually not archived unless they have been nominated to sites such as the WayBack Machine [62]. Of the sixteen venue-based electronic contact register sites documented in another paper [13], only one has been archived by the WayBack Machine. A test run at the time of writing (4 March 2023) showed that the "find a RAT" website [38] as well as the "where to buy rapid COVID test kits" website [34] were still up and running, while the RAT website operated by the Pharmacy Guild of Australia was no longer operational.…”
Section: Latency and Ephemeralitymentioning
confidence: 99%
See 3 more Smart Citations
“…Private websites, however, are usually not archived unless they have been nominated to sites such as the WayBack Machine [62]. Of the sixteen venue-based electronic contact register sites documented in another paper [13], only one has been archived by the WayBack Machine. A test run at the time of writing (4 March 2023) showed that the "find a RAT" website [38] as well as the "where to buy rapid COVID test kits" website [34] were still up and running, while the RAT website operated by the Pharmacy Guild of Australia was no longer operational.…”
Section: Latency and Ephemeralitymentioning
confidence: 99%
“…From a digital heritage perspective, this dichotomy of such ephemeral sites is illuminating. While some services will persist by virtue of being archived by the WayBack Machine, other examples of personal initiative will perish unless they have been documented by other actors [13].…”
Section: Latency and Ephemeralitymentioning
confidence: 99%
See 2 more Smart Citations
“…The legacy of the 21st century digital reality consists of all three domains: tangible, intangible and virtual. (Spennemann, 2023) The use of artificial intelligence through numerous algorithms is increasingly prevalent in the promotion of cultural heritage, and its importance can first confirm its relevance during the process of creating multimedia content. Based on predefined criteria and previous experience, Sančanin and Penjišević (2022) indicate the importance of an algorithm for recognizing visual content that could be acceptable for different purposes.…”
Section: Introductionmentioning
confidence: 99%